O ensino de didática no programa especial de formação pedagógica da UTFPR - Medianeira, PR, de 2005 a 2012 - Matté, Angela Rosina Alexius [UNESP] (2015)
This dissertation is the result of a research developed at Masters level which aimed at to recover, gather, select, organize, analyze and interpret aspects of knowledge considered to belong to the Didactics subject taught in the Special Program of Teacher Training, form Federal University of Technology of Paraná - PROFOP UTFPR - Câmpus Medianeira-PR, from 2005 to 2012. This time period was defined considering that 2005 was the year that the Federal Technological University of Paraná - UTFPR / Câmpus Medianeira-PR, before called Federal Center of Technological Education of Paraná - CEFET-PR, was constituted, and 2012 was the year immediately previous to the beginning of our research that was intended to historical approach, although the present time. We defined as specific research objectives: to compare the curriculum structures of the first version of the program (2005 to 2010) with the second version (2011 to 2012); identify possible differences and or theoretical and methodological similarities among the matters established as knowledge seen as properly from the Didactics subject in PROFOP UTFPR - Câmpus Medianeira-PR; contribute to discussions and a history about Didactics, teacher training and Education in Brazil, being able to envisage solutions to the problems of the courses and teacher training programs nowadays. In this sense, the research developed focusing on knowledge considered as proper of the Didactics subject, can be one of these opportunities, guided by the following questions: What knowledge gotten as properly form Didactics had been constituting subjects which joined the PROFOP UTFPR - Câmpus Medianeira-PR, from 2005 to 2012? How that knowledge had been materializing through several guidance and standardsetters documents of this program and is shown through spoken reports of teachers of the focused subjects? It was, therefore, a documentary research, which corpus consisted of legal documents and retrieved from...